Ethnic and religious tolerance: barrier factors and improvement measures based on Malay youth perspectives in Malaysia - Damin, Zahrul Akmal; Abdullah, Kamarulnizam; Fauzee, Mohd Sofian Omar (2021)
Ethnic and religious unity is a thing that every country wishes for not exempting Malaysia. Tolerance among the population is very much expected to achieve this. Nevertheless, ethnic and religious diversity in Malaysia is often seen as a challenge for realizing tolerance and thus creating unity. Therefore, this paper aims to analyze the barrier factors for ethnic and religious tolerance while at the same time identifying proposals for improvement measures to tolerance among the community. Hence, the Focus Group Discussion or FGD study design was used by involving 20 Malay youth informants as information providers. As a result of the analysis it can be concluded that there are six themes that exist as a barrier factor to ethnic and religious tolerance, namely (i) social gap; 38.06 percent, (ii) political debate; 16.42 percent, (iii) religious differences; 16.42 percent, (iv) economic inequality; 11.94 percent, (v) rights and constitution; 11.94 percent, and (vi) primordial sentiment; 5.22 percent. Meanwhile, in addressing the problem of ethnic and religious tolerance, the informants also proposed four perspectives on improvement measures i.e. (i) social empowerment; 71.19 percent, (ii) political role; 15.25 percent, (iii) the rule of law; 10.17 percent, and (iv) maintaining the image of Islam; 3.39 percent. The issues are important to be scrutinized because the practice of good ethnic and religious tolerance can unite the community, thereby driving the stability and progress of the country.